Pengaruh Harga Dan Inovasi Layanan Terhadap Volume Penjualan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Di Triizz Hotel Semarang - Shonda Paulina Martines; Bayu Kurniawan; Ratih Hesty Utami Puspitasari (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to find out whether there is an influence of Price and Service Innovation on Sales Volume with Customer Satisfaction as an Intervening Variable at Triizz Hotel Semarang. This type of research is quantitative research. This research uses primary data by taking data from distributing 100 questionnaires. The data analysis technique in this research uses (SEM) structural equation modeling using SmartPLS.The results of this research show that Price has no effect on Customer Satisfaction, Service Innovation has a positive and significant effect on Customer Satisfaction, Price has a positive and significant effect on Sales Volume, Service Innovation has a positive and significant effect on Sales Volume, Customer Satisfaction has a positive and significant effect on Sales Volume , Price on Sales Volume through Customer Satisfaction has a negative and insignificant effect, while Service Innovation on Sales Volume through Customer Satisfaction has a positive and significant effect.